Aksiologi dalam Pendidikan: Menjembatani Etika, Nilai, dan Praktik Pendidikan - Dadang Junaedi (Alpatih Harapan Semesta, 2026)
Education plays a vital role in shaping individuals and society, focusing on knowledge dissemination and character development. One important yet often overlooked aspect of education is the philosophy of education, or Axiology, which studies the values underlying education. Axiology significantly influences educational policies, curriculum development, and teaching practices, which aim not only to achieve academic success but also to foster character and morality in students. This research aims to explore and analyze the development and dynamics of research on Axiology in Education using a bibliometric approach based on Scopus data. Through systematic literature review (SLR) and bibliometric analysis, this study maps the contributions, trends, and connections between authors, countries, and institutions involved in Axiology research in education. The results show that Axiology in Education remains a significant topic, with a notable increase in publications in 2021. However, there is still a gap in the integration of local values in education and dominance in research from certain countries, such as Russia. This study also suggests prioritizing the integration of moral and ethical values in educational policies, curriculum development, and teacher training programs in the future. The findings provide insights for researchers and practitioners to further develop value-based education that is more holistic and relevant to social and cultural contexts.